2003
DOI: 10.1207/s15327914nc4602_16
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Efficacy, and Safety of Spinach Extracts

Abstract: Spinach leaves, containing several active components, including flavonoids, exhibit antioxidative, antiproliferative, and antiinflammatory properties in biological systems. Spinach extracts have been demonstrated to exert numerous beneficial effects, such as chemo- and central nervous system protection and anticancer and antiaging functions. In this review article, we present a compilation of data generated in our laboratories and those of other investigators describing the chemical composition of spinach, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 61 publications
1
57
0
1
Order By: Relevance
“…Freshly cut spinach leaves contain approximately 1,000 mg of total flavonoids per kilogram. The possible presence of flavonoid-like compounds in spinach was first reported in 1943 but nearly 20 yr elapsed before the structure of the flavonol isolated from spinach leaves was established as patuletin and the presence of spinacetin was confirmed [11]. In addition, the existence of several flavonol glycosides in a methanolic extract of spinach leaves was reported.…”
Section: Chemical Composition Of Spinachmentioning
confidence: 99%
See 2 more Smart Citations
“…Freshly cut spinach leaves contain approximately 1,000 mg of total flavonoids per kilogram. The possible presence of flavonoid-like compounds in spinach was first reported in 1943 but nearly 20 yr elapsed before the structure of the flavonol isolated from spinach leaves was established as patuletin and the presence of spinacetin was confirmed [11]. In addition, the existence of several flavonol glycosides in a methanolic extract of spinach leaves was reported.…”
Section: Chemical Composition Of Spinachmentioning
confidence: 99%
“…In addition, the existence of several flavonol glycosides in a methanolic extract of spinach leaves was reported. The occurrence of at least 10 flavonoid glycosides has now been reported in spinach [11]. These are glucuronides and acylated di-and triglycosides of methylated and methylene dioxide derivatives of 6-oxygenated flavonols [11].…”
Section: Chemical Composition Of Spinachmentioning
confidence: 99%
See 1 more Smart Citation
“…This NAO contains polyphenols, which include phenolic acids (p-coumaric acid derivatives) and the glucuronic acid derivatives of flavonoids [26]. We have shown that NAO has antioxidative [26,27], antiproliferative [28], and antiinflammatory properties [29][30][31][32][33] in various biological systems. Spinach flavonoids have been shown to have strong antimutagenic potential and were found beneficial in a Tg.AC mouse model [33].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that NAO has antioxidative [26,27], antiproliferative [28], and antiinflammatory properties [29][30][31][32][33] in various biological systems. Spinach flavonoids have been shown to have strong antimutagenic potential and were found beneficial in a Tg.AC mouse model [33]. Furthermore, spinach NAO has been reported to have a protective effect in various animal models for diseases such as doxorubicin-induced cardiotoxicity [30], skin papilloma [31], and lipopolysaccharide-induced septic shock [29,32].…”
Section: Introductionmentioning
confidence: 99%